Analysis of energy balance and global warming potential in tangerine (Citrus tangerina Tanaka) orchards versus soybean (Glycine max (L.) Merr.) production system - Seyed Saeed HOSSEINI (University of Ljubljana, Biotechnical Faculty, 2021)
With the aim of evaluation and comparison of the greenhouse gas emissions from soybean and tangerine production in Golestan province, Iran, a pilot experiment was carried out. In this experiment, 43 fields of soybeans and 43 orchard tangerines were selected by various management in the province using questionnaires. The greenhouse gas emissions were examined using the Global Warming Potential (GWP). The results of this study showed that fossil fuel was the highest energy consumption in the production of soybeans (6906.5 MJ ha-1) and tangerines (17205.1 MJ ha-1). The lowest amount of energy consumption among inputs was related to micro fertilizers, that was 9 MJ ha-1 for soybeans and 17.6 MJ ha-1 for tangerine. In both of production system, the most energy consumed was shown for the harvesting sector. Irrigation and planting were the highest contributors to greenhouse gas emissions in soybean field by 387.7 and 109.4 kg CO2 ha-1, respectively; while in the tangerine production, the most greenhouse gas emissions were related to irrigation and harvesting process by 5828.4 and 394.7 kg CO2 ha-1. In general, input energy in soybean and tangerine were 17512.8 and 33879.8 MJ ha-1, total output energy was calculated 48310.5 and 105463 MJ ha-1. Finally, the energy use efficiency was computed for soybean and tangerine 2.9 and 3.3, respectively.